Pan-Islamism of Jamaluddin Al Afghani and as an Effort to Overcome the Destruction of Dynastic Politics: Analysis of Islamic Worldview - Asrofil Fuad (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Dynastic politics is becoming a hot topic among the public at this time because dynastic politics is considered to damage the democratic system that has been running in the country. Dynastic politics must be prevented immediately because it has the potential to have a bad impact on the government of a country. Jamaluddin Al Afghani is one of the Islamic scholars engaged in politics. With his intelligence that he had since childhood, he could create ideas that could have a great influence on Muslims, namely Pan-Islamism. This article aims to present the idea of Pan-Islamism as a means of deterrence against the ongoing dynastic politics. In writing this article, the author uses qualitative descriptive methods by collecting primary and secondary data. With the idea of Pan-Islamism, dynastic politics is expected to be prevented by using five ways including: empowerment of the people in the political process, supervision and accountability, resistance to nep